KAJIAN KEPUASAN MASYARAKAT TERHADAP PROGRAM JAMINAN KESEHATAN NASIONAL (JKN) - Muhammad Khozin (JHeS (Journal of Health Studies), 2017)
Abstract :Some bad experiences toward the service of healthcare agency which was held by the Government made it difficult for the society to put their trusts on its quality of the new program from National Healthcare Assurance or JKN by Healthcare and Social Security Agency or BPJS Kesehatan. This study was aimed to assess the level of people’s satisfactions in Balangan Regency toward the programs of National Healthcare Assurance or JKN and some factors that influenced them. The method of this study was the mixed one between qualitative and quantitative study. Meanwhile, the data types were primary and secondary data. Therefore, the data was gathered from questionnaire, interview and literature review. Besides, the population of the study was the Balangan society who had been the members of National Healthcare Assurance (JKN) program. Then, they were chosen to be the sample using Proportionate Stratified Random Sampling method. Thus, the data was processed using Descriptive Statistics Analysis Technique and Multiple Linear Regression Analysis. Keywords :Jaminan Kesehatan Nasional (JKN), Quality of Service, Public Service